2020
DOI: 10.1177/2374373520964045
|View full text |Cite
|
Sign up to set email alerts
|

Patient Experience of Obstetric Care During the COVID-19 Pandemic: Preliminary Results From a Recurring National Survey

Abstract: The experience of pregnant and postpartum patients continues to evolve during the COVID-19 pandemic. Limited clinical data and the unknown nature of the virus’ impact and transmission routes have forced constant changes to traditional care delivery. Dependence on telehealth technology such as telephonic and videoconferencing has surged, and patients’ willingness to visit traditional health care facilities has plummeted. We set out to create an ongoing surveillance system to monitor changes to prenatal and obst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 5 publications
2
28
0
Order By: Relevance
“…Many who had never considered community birth sought out the option for a home or birth center birth 20 . Similarly, recent results from a national survey demonstrated that nearly 1 in 4 pregnant respondents (24.5%) considered home birth as an option 3 . Those who opted for community birth in our study, often reflected that their birth experience felt transformative.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Many who had never considered community birth sought out the option for a home or birth center birth 20 . Similarly, recent results from a national survey demonstrated that nearly 1 in 4 pregnant respondents (24.5%) considered home birth as an option 3 . Those who opted for community birth in our study, often reflected that their birth experience felt transformative.…”
Section: Discussionsupporting
confidence: 67%
“…13 In addition to these validated measures, the questionnaire asked about demographics, choice of birth setting, anticipatory guidance related to COVID protocols, delivery mode, perceived stress, and birth experience. Participants rated on a Likert scale their levels of stress (1-10) and satisfaction (1-5) and how informed they felt during their experiences of pregnancy and birth (1)(2)(3)(4)(5)(6). Lower scores indicated more positive experiences (less stress, higher satisfaction, and feeling better informed).…”
Section: Methodsmentioning
confidence: 99%
“…Participants may have had to choose between caring for children (now home from school due to the pandemic) or other caregiving responsibilities and attending in-person appointments with limits to those accompanying them. A large study that included pregnant participants ( n = 1829) reported that 10% of that sample used telehealth at some point during the pregnancy, which is consistent with our findings (12%) 28. Changes to prenatal care delivery with telehealth and other remote modalities presented a problem for both personal and practical reasons.…”
Section: Discussionsupporting
confidence: 89%
“…However, such communication may have become more difficult given the spread of the pandemic, the strain it put on healthcare services, and the introduction of lockdown measures. In the United States, a survey conducted between mid-March and mid-May 2020 showed that almost one-third of pregnancy monitoring visits were changed, cancelled or postponed [ 13 ]. In France, half (48.9%) of the pregnant women included in the Covimater cross-sectional study reported at least one postponement or cancellation of a consultation or pregnancy check-up during the country’s first lockdown (from 17 March to 11 May 2020), whether on their own initiative (23.4%), or that of a hospital/health professional (36.3%) [ 14 ].…”
Section: Introductionmentioning
confidence: 99%